2019
DOI: 10.1002/anie.201904312
|View full text |Cite
|
Sign up to set email alerts
|

Robust Microporous Metal–Organic Frameworks for Highly Efficient and Simultaneous Removal of Propyne and Propadiene from Propylene

Abstract: Simultaneous removal of trace amounts of propyne and propadiene from propylene is an important but challenging industrial process.W ereport herein aclass of microporous metal-organic frameworks (NKMOF-1-M)w ith exceptional water stability and remarkably high uptakes for both propyne and propadiene at lowp ressures. NKMOF-1-M separated at ernary propyne/propadiene/propylene (0.5 :0.5 :99.0) mixture with the highest reported selectivity for the production of polymer-grade propylene (99.996 %) at ambient temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 38 publications
(33 reference statements)
0
52
0
1
Order By: Relevance
“…The energetic „sweet spot“ for C 2 H 2 capture under ambient conditions is controlled by sorbent–C 2 H 2 binding interactions, which result from pore size and pore chemistry. This is exemplified by the current benchmark sorbents for CO 2 /N 2 , CO 2 /CH 4 , C 2 H 2 /C 2 H 4 , C 2 H 4 /C 2 H 6 , C 2 H 6 /C 2 H 4, propadiene/propylene, propyne/propylene, ternary propyne/propadiene/propylene, and C 4 olefins . Interestingly, the leading sorbents are ultramicroporous with tight binding sites, in which sorbate binding is driven by pore chemistry: strong electrostatics, H‐bonding sites, or open metal sites .…”
Section: Methodsmentioning
confidence: 93%
“…The energetic „sweet spot“ for C 2 H 2 capture under ambient conditions is controlled by sorbent–C 2 H 2 binding interactions, which result from pore size and pore chemistry. This is exemplified by the current benchmark sorbents for CO 2 /N 2 , CO 2 /CH 4 , C 2 H 2 /C 2 H 4 , C 2 H 4 /C 2 H 6 , C 2 H 6 /C 2 H 4, propadiene/propylene, propyne/propylene, ternary propyne/propadiene/propylene, and C 4 olefins . Interestingly, the leading sorbents are ultramicroporous with tight binding sites, in which sorbate binding is driven by pore chemistry: strong electrostatics, H‐bonding sites, or open metal sites .…”
Section: Methodsmentioning
confidence: 93%
“…丙烯是工业产量仅次于乙烯的重要烯烃原料, 主 要用作聚合单体生产如聚丙烯等下游产品, 被广泛用 于塑料、制药、纺织品、涂料等国民经济各个行业 [1][2][3][4] 。目前,丙烯生产主要通过蒸汽裂解的方式进行, 该技术会难以避免地引入少量丙炔和丙二烯等杂质 气体,严重影响后续的丙烯聚合过程,因此,实现丙 烯与丙炔和丙二烯有效分离是丙烯纯化过程中的关 键 [5,6] 。现有的丙炔/丙烯、丙二烯/丙烯分离技术主要 是选择性催化加氢, 通过将丙烯中的丙炔或丙二烯转 化为丙烯,从而达到丙烯纯化的效果,但该过程存在 丙烯过度加氢得到副产物丙烷的问题, 同时存在分离 能耗大、成本高等缺点,因此需要开发更为经济有效 的分离方法 [7,8] 。 近年来, 以离子液体作为溶剂的吸收分离技术受 到广泛关注 [9][10] 。 吸收分离技术流程简单, 处理量大, 同时离子液体具有极低的蒸气压、 良好的化学稳定性 和丰富的结构可设计性, 可以克服常规溶剂的局限性, 使吸收过程无溶剂损失,同时易于回收利用,无交叉 污染 [11][12] 。在气体分离领域,离子液体已被研究应用 于 CO2 捕集 [13][14][15][16] 、NH3 捕集 [17] 、H2S 和 SO2 脱除 [18][19][20] 以及低碳烃分离等方面 [21][22][23][24] 。其中,Kim 等人测定了 C2-C3 炔烃烯烃在几种咪唑类离子液体中的溶解度 [25] , 其中 [ [26][27] ,有望与 丙炔和丙二烯分子发生相对较强的氢键相互作用, 获 得较高的溶解度 [28] , 同时引入结构不对称的三丁基乙 基鏻阳离子([P4442] + )能显著降低离子液体粘度,且 合成的离子液体具备良好的热稳定性,分解温度在 580 K 左右 [29][30] [27][28] 进行溶解度测试前, 合成的离子液体经过 1 mbar [29][30]…”
Section: 引言unclassified
“…Chronology of key developments with respect to the use of PCNs for C3 hydrocarbon separation (reprinted with permission from Refs. 4,71,78,87–97. Copyright 2009, American Chemical Society; Copyright 2009, Elsevier B.V.; Copyright 2010, American Chemical Society; Copyright 2012, American Association for the Advancement of Science; Copyright 2016, American Association for the Advancement of Science; Copyright 2016, American Chemical Society; Copyright 2017, Elsevier B.V.; Copyright 2018, Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim; Copyright 2018, Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim; Copyright 2018, Elsevier B.V.; Copyright 2019, The Royal Society of Chemistry; copyright 2019, Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim; Copyright 2020, American Chemical Society; Copyright 2020, American Chemical Society).…”
Section: Chronology Of the Development Of Pcns For C3 Hc Separationmentioning
confidence: 99%
“…At the time, ZU‐62 displayed a new record for C 3 H 4 (PD) uptake (1.74 mmol/g), high C 3 H 4 uptake (1.87 mmol/g), and very low uptake, 0.05 mmol/g, for C 3 H 6 at 5000 ppm and 298 K. This was attributed to the presence of a C 3 H 4 ‐selective Site III and a C 3 H 4 (PD)‐selective Site I. Breakthrough tests for C 3 H 4 /C 3 H 4 (PD)/C 3 H 6 (0.5:0.5:99) mixtures afforded an ultra‐pure stream of C 3 H 6 (over 99.9999%) through a one‐step purification process. Subsequently, Peng et al 4 reported two ultra‐microporous PCNs, NKMOF‐1‐M (M = Cu, Ni), which exhibited benchmark selectivity for ternary C 3 H 4 /C 3 H 4 (PD)/C 3 H 6 (0.5:0.5:99) mixtures. Recently, a Ca‐based MOF studied by Li et al 97 was also reported to simultaneously remove C 3 H 4 and C 3 H 4 (PD) from a ternary mixture of C 3 H 4 /C 3 H 4 (PD)/C 3 H 6 .…”
Section: Chronology Of the Development Of Pcns For C3 Hc Separationmentioning
confidence: 99%